Low Birth Weight and Childhood Pneumonia in Sumatra, Indonesia: A Cross-Sectional Analysis of the 2023 Indonesian Health Survey - Putri, Aulia; Widoyo, Ratno; DJafri, Defriman (Jurnal Kesmas Jambi, 2026)
Low birth weight (LBW) is a well-established early-life biological risk factor for respiratory infections; however, subnational evidence examining its role in childhood pneumonia in Indonesia remains limited. This study aimed to examine the association between low birth weight and pneumonia among children aged 12–59 months in Sumatra, Indonesia, while accounting for demographic, health service, and environmental factors. A cross-sectional study was conducted using data from the 2023 Indonesian Health Survey (IHS). The analysis included 21,466 children aged 12–59 months residing in Sumatra. Pneumonia status and low birth weight were defined according to the SKI standard definitions. Multivariable logistic regression analyses were performed using sampling weights to account for the complex survey design. Adjusted odds ratios (aORs) and 95% confidence intervals (CIs) were reported. The prevalence of pneumonia among children aged 12–59 months in Sumatra was 1.0%. Children with a history of low birth weight had markedly higher odds of pneumonia compared with those born with normal birth weight (aOR 14.9; 95% CI 9.2-24.1). Household cooking fuel use was identified as a confounding factor, but not as an interaction. Other factors, including vitamin A supplementation, immunization status, and area of residence, were not identified as confounding or interacting factors. Low birth weight is a strong determinant of pneumonia among children aged 12–59 months in Sumatra. Reducing childhood pneumonia requires integrated strategies addressing both early-life biological vulnerability and modifiable household environmental exposures.